Pengaruh Struktur Modal Dan Likuiditas Terhadap Nilai Perusahaan Dengan Profitabilitas Sebagai Variabel Intervening Pada Perusahaan Manufaktur Sub Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Periode 2020-2024 - Aulia Darmaya Putri (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study aims to examine the effect of capital structure and liquidity on firm value with profitability as an intervening variable in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2020-2024. The sampling technique used purposive sampling with a total of 28 companies and 140 observations. Data analysis techniques used multiple linear regression analysis and path analysis with SPSS 26. The results showed that simultaneously (F-test) capital structure and liquidity have a significant effect on profitability with F count 8.918 > F table 3.062 (sig. 0.000), likewise capital structure, liquidity, and profitability have a simultaneous significant effect on firm value with F count 31.131 > F table 2.671 (sig. 0.000). Partially (t-test), capital structure has a negative and significant effect on profitability (t = -3.180; sig. 0.002), while liquidity does not have a significant effect on profitability (t = -0.930; sig. 0.354). Capital structure has a positive and significant effect on firm value (t = 2.578; sig. 0.011), while liquidity does not affect firm value (t = -0.053; sig. 0.958). Profitability has a positive and significant effect on firm value (t = 9.549; sig. 0.000). Adjusted R² value for equation 1 is 0.102 (10.2%) and equation 2 is 0.394 (39.4%). The mediation analysis results show that profitability cannot mediate the effect of capital structure on firm value (direct effect 0.299 > indirect effect 0.003), but profitability can mediate the effect of liquidity on firm value (indirect effect 0.001 > direct effect -0.006). This research provides practical implications for company management to optimize capital structure and increase profitability to maximize firm value.